First Report of Exserohilum rostratum Causing Brown Spot on Spartina alterniflora in China - Wei, Youjing (Plant disease, 2024)
Spartina alterniflora Loisel, a perennial grass, has become an invasive species in China's coastal wetlands (Zhang et al. 2018). In July 2021, brown spot symptoms were observed on S. alterniflora in a coastal wetland (21°45'48″N, 108°44'00″E) in Beihai City, Guangxi Province, China. The disease affected approximately 50% of the plants in the surveyed area (0.2 ha) and was also observed in other regions of Beihai. It caused brown lesions with a gray or whitish center on the leaves and stems of S. alterniflora. As the disease developed, it ultimately led to leaf shedding and plant death. To isolate the causal agent, 18 fragments (~ 5 mm) from six symptomatic plants (3 leaf pieces per plant) were surface sterilized with 1% NaOCl solution for 2 min and rinsed three times with sterilized water. Subsequently, the tissues were placed on potato dextrose agar (PDA) medium supplemented with chloramphenicol (0.1 g/liter) and incubated at 28°C for three days. The hyphal tips were transferred onto fresh PDA to obtain pure cultures. A total of 25 isolates were obtained, 20 of which shared similar morphologies, while the remaining five exhibited distinct morphological characteristics and were non-pathogenic to S. alterniflora. Three isolates (MC16.1.3, MC16.6.2, and MC16.8.3) were randomly selected from the 20 for further investigation. The colonies on PDA were flat with dense aerial mycelia. The colony margins were entire, light brown in the centre, white to grey at the margin; reverse dark brown in the centre, gray at the margin. Conidia were straight to slightly curved, light olive-brown to dark olive-brown, septate, measured 33.5 to 79.1 μm × 10.4 to 18.7 μm (average 52.9 × 14.4 μm, n = 100), with a distinctly protruding hilum swelled from the basal cell. For molecular identification, the genomic DNA was extracted from mycelium on PDA using the CTAB method (Guo et al. 2000). The internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and translation elongation factor 1 alpha (TEF1-α) genes were amplified and sequenced with the primer pairs ITS1/ITS4 (White et al. 1990), GPD1/GPD2 (Berbee et al. 1999), and EF1-983/EF1-2218 (Rehner et al. 2005), respectively. A BLAST analysis revealed that the ITS (OR516787-9), GAPDH (OR523686-8), and TEF-α (OR523683-5) had 99.1 to 99.7% identity with those of E. rostratum strains BRIP 11417 (LT837836, LT882553, and LT896656) and CBS 128061 (KT265240, LT715900, and LT896658) (Hernández-Restrepo et al. 2018). Based on the concatenated sequences, a phylogenetic tree generated by PhyloSuite software (Zhang et al., 2020) through Bayesian inference (BI) and Maximum Likelihood (ML) methods placed the isolates within E. rostratum. These morphological characteristics and molecular analyses confirmed the pathogen as E. rostratum (Hernández-Restrepo et al. 2018; Kaboré et al. 2022). To confirm pathogenicity, a conidial water suspension (~ 1 × 106 conidia/ml) of each of the three strains was inoculated on nine healthy S. alterniflora plants that had been grown for six months. Control plants were treated with sterile water. All plants were then enclosed in plastic bags and incubated in a greenhouse at 28°C. Six days after inoculation, the plants exhibited symptoms similar to those observed in nature. The control plants developed no symptoms. These experiments were replicated three times with similar results. To fulfill Koch's postulates, E. rostratum was consistently re-isolated from symptomatic tissue and confirmed by morphology and sequencing, whereas no fungus was isolated from the control plants. In recent years, S. alterniflora has posed a serious threat to the indigenous biodiversity of wetland ecosystems (Zhang et al. 2018). To our knowledge, this is the first report of E. rostratum causing brown spot on S. alterniflora worldwide